Message in a Bottle - Matos, M. M. (Open Schools Journal for Open Science, 2020)
This project aims to develop a culture of affection, with a view to humanization and the development of the feeling of belonging in the relations of the school community, based on the exercise of citizenship. Messages, prepared by students in Portuguese classes, were placed in reused plastic bottles, decorated for this purpose in Visual Education classes. The messages were translated by students to English, French and German classes and by various elements of the school community, totalling nine different languages. The bottles were successfully delivered by the school to health care institutions. This project has been implemented since the 2015-2016, and 416 messages were distributed to 20 stakeholders. We want messages to be sent to as many people as possible, both at regional, national and international level.